COMPLICAÇÕES DA COVID-19 NA SAÚDE DE PESSOAS COM DIABETES MELLITUS - Isidoro, Geovanna Maria (2025)
Introduction: People diagnosed with diabetes mellitus are more likely to develop complications when affected by Covid-19, as they present an uncontrolled inflammatory response, increased coagulation and enzymes responsible for tissue damage. Objective: Identify the complications of Covid-19 on the health of people with diabetes mellitus. Materials and method: Quantitative, descriptive and cross-sectional research. Study carried out in a municipality in the south of Minas Gerais, through semi-structured interviews and data recording in the KoBo Toolbox tool. Results: 156 people who tested positive for Covid-19 and confirmed diagnosis of diabetes mellitus participated in the study. Detection of the virus was mainly carried out by searching for the antigen in laboratory tests. The main complications caused by Covid-19 in people with diabetes mellitus were hematological, followed by neurological, vascular, cardiac and respiratory complications. Conclusion: The complications of Covid-19 are extremely significant for people with diabetes mellitus, affecting their physical, mental and social well-being, which points to the relevance of longitudinal monitoring for effective care actions consistent with the needs of these people and their families.